TESTING OF EMULSION VACCINES BASED ON WHITE OILS OBTAINED AS A RESULT OF HYDROCATALYTIC PROCESSING OF OILSTOCK - I. V. Pigoleva; A. S. Sharypov; T. N. Shabalina; S. V. Zaglyadova; M. V. Kitova; S. A. Antonov; V. V. Mikhalishin; V. A. Starikov; D. V. Mikhalishin (Ветеринария сегодня)
The paper demonstrates the possibility to use white mineral oils resulting from hydrocatalytic processing of unconverted vacuum gas oil as a basis for an oil adjuvant used in the production of FMD vaccines intended for livestock. Samples of the developed white oils were tested for their reactogenicity and pyrogenicity, and emulsion vaccines were tested for their reactogenicity, potency, and emulsion stability. Tests results were compared with the ones for a foreign analogue. Blood samples were taken from animals before vaccination and 14 days after it to obtain sera which were further tested for FMD antibodies using VNT. Assessment of the white oil sample reactogenicity demonstrated that sample BM 1.4 obtained during hydroisomerization was the least reactogenic. Sample V-BM 1.4 demonstrated the best result in comparison with other samples within the group as well as in comparison with the control sample during the emulsion stability test. According to the potency test results, the emulsion vaccine based of the white oil sample BM 1.4 demonstrated the greatest difference in antibody titers in 14 days - 4.15 log2, while the one based on the control sample - 3.50 log2. This means that it the use of this vaccine results in 17.7-fold increase in FMD antibodies, while the use of control emulsion vaccine in 11.3-fold increase. Vaccines based on BM 1.3 and BM 2.2 oil samples demonstrated lower performance in comparison with the control vaccine in terms of these parameters.